Self-Concept and Self-Efficacy Beliefs as Determinants of Success among Equality Non-Formal Education Learners - Kamilin Kamilin; Muhadjir Effendy; Rosyid Al Atok; Ach. Rasyad (MASI Mandiri Edukasi, 2026)
Background: Successful implementation of non-formal equality education requires learning centers to produce competent and independent learners. Gap: While much attention has been given to external factors and correcting educational weaknesses, there is a critical need to understand how internal self-constructs actively build learner competencies. Method: Therefore, the present study aims to explain the specific determinants of learner success by examining self-concept and self-efficacy beliefs. A qualitative phenomenological design was employed, utilizing in-depth, semi-structured interviews. Participants: Participants included adult learners such as farmers, industrial workers, and previous school dropouts enrolled in the vocational Package C (high school equivalence) program at Community Learning Centers (CLCs) in Malang District. Findings: Thematic content analysis revealed that successful learner development is rooted in distinct self-concept components, including self-image, idealism, and study-orientation. Additionally, self-efficacy manifests concretely through learners' ability to complete tasks, manage time, and respond positively to tutors' verbal persuasion. Implications & Contribution: Rather than merely identifying a broad